Hydroxyurea utilization among individuals with sickle cell disease in Tennessee: a pooled analysis of claims data - Mukhopadhyay, Ayesha; Smeltzer, Matthew P.; Dudley, Judy; Badawy, Sherif M.; Mathias, Joacy G.; Plaxco, Allison P.; Ray, Meredith A.; Wiese, Andrew D.; Stevens, Walter I.; Gurney, James G.; Nwosu, Chinonyelum; Porter, Jerlym S.; et al. (Frontiers in Pharmacology, 2025)
ImportanceHydroxyurea reduces severe disease among individuals living with sickle cell disease (SCD). These individuals experience high acute care utilization, but the associations between patterns of hydroxyurea utilization and healthcare utilization are not well investigated.ObjectiveThis study aimed to determine the association between hydroxyurea use and healthcare utilization among individuals with SCD in Tennessee (TN).DesignWe conducted a population-based, retrospective cohort study of individuals with SCD using secondary data analysis of Tennessee Medicaid, Medicare, and BlueCross BlueShield of Tennessee (BCBS-TN).ParticipantsA total of 4,901 individuals with SCD were included in the study.ExposureHydroxyurea adherence was estimated using the medication possession ratio (MPR).Main Outcomes and measuresThe incidence rate ratios of hospitalizations, emergency department visits, and mortality were calculated using negative-binomial models.ResultsThe prevalence of hydroxyurea prescription dispensation for the state was low (21% for TennCare, 21% for Medicare, and 17% for BCBS-TN). In TennCare and BCBS-TN, those younger than 18 had more hydroxyurea utilization, and individuals with HbSS or HbSβ0 thalassemia filled more hydroxyurea than those with other subtypes (30.5% in TennCare and 23.4% in BCBS-TN). The MPR for the entire state was 19.7%. There was a dose–response relationship between hydroxyurea adherence and the incidence of acute healthcare utilization, except in 18–25-year-olds. We also found lower mortality in those with higher hydroxyurea adherence.Conclusion and relevanceIn our pooled statewide analysis, hydroxyurea MPR was low. Higher hydroxyurea use was associated with decreased acute healthcare utilization and lower mortality. Interventions to support patient adherence and provider prescribing are required to improve health outcomes among individuals with SCD.